The arts & crafts movement in Europe & America : Design for the modern world - Kaplan, Wendy; Ogata, Amy F.; Stavenow-Hidemark, Elisabet; Witt-Dorring, Christian (New York Los Angeles : Thames & Hudson Los Angeles County Museum of Art, 2004)
This catalogue was published in conjunction with the exhibition "The arts & crafts movement in Europe & America, 1880-1920: Design for the modern world" organized by the Los Angeles County Museum of Art and made possible by Max Palevsky (bron: achterzijde titelpagina).
Engels
kunstcatalogus
Keywords: Arts and Crafts; Europa; Amerika